Discordance in cathepsin B and cystatin C expressions in bronchoalveolar fluids between murine bleomycin-induced fibrosis and human idiopathic fibrosis. Issue 1 (December 2016) - Kasabova, Mariana; Villeret, Bérengère; Gombault, Aurélie; Lecaille, Fabien; Reinheckel, Thomas; Marchand-Adam, Sylvain; Couillin, Isabelle; Lalmanach, Gilles
Abstract The activity of cysteine cathepsin B increased markedly in lung homogenates and in bronchoalveolar lavage fluids (BALF) of the mouse model of bleomycin-induced lung fibrosis after 14 days of challenge. In contrast the level of the cysteine cathepsin inhibitor cystatin C was unaffected in BALF of wild-type and cathepsin B-deficient mice. Therefore, murine cystatin C is not a reliable marker of fibrosis during bleomycin-induced lung fibrosis. Current data are in sharp contrast to previous analysis carried on human BALF from patients with idiopathic pulmonary fibrosis, for which the level of cathepsin B remained unchanged while cystatin C was significantly increased.